Persepsi guru terhadap sistem pembelajaran inklusi di sekolah dasar - Anggadewi, Brigitta Erlita Tri; Evanjeli, Laurensia Aptik (Jurnal Psikologi Udayana, 2022)
Inclusive learning in elementary schools is increasingly being promoted by the government. Each school is expected to be able to meet the needs of students with special needs who are studying. However, the realization of inclusive schools can also be influenced by the teacher's perspective on children with special needs. So far, teachers have only followed directions from schools and schools have followed directions from the Government. It is really necessary to know how teachers actually perceive children with special needs which in the end also has an impact on their perspective on the inclusion system in schools. So this research was conducted to determine the teacher's perception. This study uses a survey method. The target respondents of this research are teachers in elementary schools who are partners with PGSD USD. Respondents were selected through a purposive sampling technique with the sample criteria being elementary school teachers who partnered with PGSD USD. The research instrument was a questionnaire with closed questions. The instrument is designed for pre-service teachers so that the instrument will go through a modification process.